The complete mitochondrial genome sequence of Aquilaria sinensis - Wang, Zheng-Feng (Mitochondrial DNA B Resour, 2021)
Aquilaria sinensis, endemic to China, is an economically important evergreen tree species and a source of agarwood. Due to the high market demand for agarwood, this species is heavily overexploited in the wild and is now listed as an endangered species. Although its nuclear and chloroplast genomes have been previously reported, little is known about its mitochondrial genome. Using the paired-end short reads generated by the Illumina sequencing platform, we assembled and herein report the mitochondrial genome of A. sinensis for future phylogenetic, evolutionary, and preservative studies. The length of the A. sinensis mitochondrial genome was found to be 341,829 bp and the GC content was 45.01%. A total of 32 protein-coding genes, 19 tRNA genes, and three rRNA genes were annotated. The phylogenetic tree indicated that A. sinensis is most closely genetically related to Vigna radiata.